Perfect equilibria in games of incomplete information - Oriol Carbonell-Nicolau (Rutgers University, Department of Economics, 2017)
We obtain conditions on the primitives of a Bayesian game with infinitely many types and/or strategies that ensure the existence of a perfect Bayes-Nash equilibrium. The main existence results are illustrated in the context of all-pay auctions.
Keywords: C72; 330; infinite game of incomplete information; perfect Bayes-Nash equilibrium; payoff security